Recombinatorial Cloning Using Heterologous Lox Sites - Siegel, Robert W.; Velappan, Nileena; Pavlik, Peter; Chasteen, Leslie; Bradbury, Andrew (Genome Research, 2004)
Recombination systems based on λ and Cre/loxP have been described to facilitate gene transfer from one vector to another in a high-throughput fashion, avoiding the bottlenecks associated with traditional cloning. However, no system described to date is suitable for the cloning of affinity reagents selected from display libraries, which requires that the recombination signals flanking the affinity reagent are translated with a minimum impact on functionality. As affinity reagents will be essential tools in the functional characterization of proteomes, and display technologies represent the most effective means to generate such affinity reagents on a genomic scale, we developed a Cre/loxP-based system, using mutually exclusive heterologous loxP sites placed 5′ (Lox 2372) and 3′ (Lox WT) of an affinity reagent (scFv). The translated lox sites have minimal impact on scFv expression or functionality, and, in association with a conditionally lethal gene (SacB) permit efficient, high-fidelity transfer to destination vectors. This approach will considerably facilitate the high-throughput downstream use of affinity reagents selected by display technologies, as well as being widely applicable to general recombinatorial cloning for genomic purposes.